Penatalaksanaan Fisioterapi padaCervical Root Syndrome di RSUD dr. Moewardi Surakarta - Setya Nugroho, Galih Priambudi; , Arif Pristianto, SSt.FT.,M.Fis (2017)
Background: Cervical root syndrome is a symptom that causes neck pain that radiates up to the arm according to irradiated nerve roots distribution and limited range of motion of joints that can decrease functional activity. Objective: To know the management of Physiotherapy in reducing pain, increase the scope of joint motion and increase functional activity in cervical root syndrome case by using micro wave diathermy modalities, Trancutaneus Electrical Nerve Stimulation and contract relax streching exercise. Results: After the therapy for 6 times obtained the results of the pain assessment on the sailent pain did not change because of no pain. Initial T1 pain is worth 5 and T6 end is worth 2. While the T1 motion pain is worth 5 and the final T6 is worth 3. The increase of joint motion scope in flexion motion which originally T1 is worth 2 to T6 is worth 3, ROM lateral flexion increase which originally T1is worth 3 to T6 is worth 4, the increase in rotation of the original sinistra T1 is worht 2 to T6 is worth 4. Increased functional activity using NDI get T1 total of 20 to T6 total 13. Conclusion: Micro Wave Diathermy, Trancutaneus Electrical Nerve Stimulation and contract relax streching exercise can reduce pain, can increase the scope of motion of the joints in the neck and can increase functional activity.